2021
DOI: 10.1001/jamanetworkopen.2021.0307
|View full text |Cite
|
Sign up to set email alerts
|

Gene Sequencing for Pathogenic Variants Among Adults With Breast and Ovarian Cancer in the Caribbean

Abstract: IMPORTANCE Rates of breast and ovarian cancer are high in the Caribbean; however, to date, few published data quantify the prevalence of inherited cancer in the Caribbean population. OBJECTIVE To determine whether deleterious variants in genes that characterize the hereditary breast and ovarian cancer syndrome are associated with the development of breast and ovarian cancer in the English-and Creole-speaking Caribbean populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
(53 reference statements)
0
25
0
1
Order By: Relevance
“…The prevalence of 83.9% by late-stage diagnosis mentioned earlier (Patient Demographics) corresponds to Fadelu et al [ 33 ] whose cohort had 53.4% late-stage tumors (given that 23.5% were of an unknown stage). In addition, George et al [ 71 ] found the highest percentage of advanced-stage disease in Haiti in comparison to other Caribbean countries studied, where 64.7% (44 of 68) had stage III/IV BC. In 2010, Kobetz et al [ 72 ] paralleled 45% regional/distant metastatic BC cases at diagnosis among Haitians living in Miami to only 10% among comparable ethnic/sociodemographic neighboring groups.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of 83.9% by late-stage diagnosis mentioned earlier (Patient Demographics) corresponds to Fadelu et al [ 33 ] whose cohort had 53.4% late-stage tumors (given that 23.5% were of an unknown stage). In addition, George et al [ 71 ] found the highest percentage of advanced-stage disease in Haiti in comparison to other Caribbean countries studied, where 64.7% (44 of 68) had stage III/IV BC. In 2010, Kobetz et al [ 72 ] paralleled 45% regional/distant metastatic BC cases at diagnosis among Haitians living in Miami to only 10% among comparable ethnic/sociodemographic neighboring groups.…”
Section: Reviewmentioning
confidence: 99%
“…Immunohistochemistry tests for receptor status (ER/HER2/PR) of tumors are unavailable in Haiti and are outsourced in the United States (reliant on patient affordability) making clinicopathologic data limited in both quantity and quality [ 32 , 71 ]. DeGennaro et al [ 32 ] reported invasive ductal carcinoma in 87.3% of women, with a prevalence of 51.8% ER+ tumors (supposed overestimation due to over fixation), 19.6% HER2+ tumors, and 38.5% TNBC.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations